Amphiphilic carbon dots and preparation method thereof, surfactant composition and preparation method thereof
By preparing amphiphilic carbon dots with hydrophilic groups and hydrophobic alkane chains and using them in combination with cationic surfactants, the problem of insufficient surfactivity of carbon dots is solved, and the amphiphilic regulation of carbon dots and significant surfactivity effect is achieved.
Patent Information
- Application Number
- CN202510108426.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to simultaneously regulate the surface hydrophilicity and hydrophobicity of carbon dots, resulting in the lack of significant surfactivity of carbon dots.
By using C12-C18 long-chain fatty acids or their glycerol mixtures as precursors, combined with hydrogen peroxide as an oxidant, and reacting at 160-210°C, amphiphilic carbon dots with hydrophilic groups and hydrophobic alkane chains were prepared and used in combination with cationic surfactants.
实现了碳点的两亲性调控,使其具有显著的表面活性,能够在水和有机相中均匀分散,具备明亮的蓝色荧光,耐高温,并显著提高了除油效果。
Smart Images

Figure CN119898759A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon dot materials, and relates to amphiphilic carbon dots and preparation methods thereof, surfactant compositions and preparation methods thereof. Background Art
[0002] As an important member of the carbon-based fluorescent nanomaterial family, carbon dots have the characteristics of easy availability of raw materials, non-toxicity, adjustable luminescence, strong chemical stability, and easy functionalization. They are widely used in biological imaging, chemical sensing, photoelectrocatalysis, intelligent anti-counterfeiting and other fields.
[0003] It is generally believed that the center of carbon dots is usually a crystalline sp 2 Or amorphous sp 3 The hybridized carbon core has groups such as amino, hydroxyl, and carboxyl groups on the surface. Existing work is mostly focused on the study of the luminescent properties of carbon dots, and the regulation of the hydrophilicity and hydrophobicity of the surface of carbon dots is still in its infancy. For example, amine-modified hydrophilic carbon dots were prepared using glucose and 3-aminopropyltriethoxysilane as raw materials; without the addition of surfactants, carbon dots as oil displacement agents showed a high oil recovery efficiency of 54.09%, which was significantly higher than the oil recovery efficiency of water (30.25%) and nano-silica (36.45%) systems. For another example, hydroquinone and urea were selected as precursors, and carbon dots were prepared by solvothermal method; by regulating the type and dosage of precursors, reaction solvents, carbonization temperature and insulation time, the surface state of carbon dots can be accurately controlled, and then hydrophilic, hydrophobic and amphiphilic carbon dots can be obtained, and successfully applied to the detection of alcohol content in liquor. For another example, amphiphilic carbon dots were prepared by plasma induction using egg yolks with a high fat content. An appropriate amount of organic dyes was doped into the solution to achieve manipulation of multicolor pattern photoluminescence, which can be used as fluorescent carbon ink for printing multifunctional fluorescent images. However, the research on the amphiphilicity of carbon dots in these works mainly focused on the solubility of carbon dots in different solvents. "Amphiphilicity" and "surface activity" are not the same concept. Most amphiphilic carbon dots do not have surface activity and cannot be used as surfactants. Therefore, how to simultaneously obtain the hydrophilicity of the hydrophilic groups on the surface of the carbon dots and the hydrophobicity of the lipophilic groups, so that the carbon dots have a special structure, thereby giving the carbon dots significant surface activity has become the key. Summary of the invention
[0004] The present invention discloses amphiphilic carbon dots and preparation methods thereof, surfactant compositions and preparation methods thereof, aiming to partially or completely solve the problems existing in the prior art. The technical solutions of the present invention are as follows:
[0005] In a first aspect, an amphiphilic carbon dot comprises a crystalline sp 2 Or amorphous sp 3The hybridized carbon has a conjugated structure in the carbon core portion and has a hydrophilic group and a C12-C18 hydrophobic alkane chain on the surface, wherein the hydrophilic group includes an amino group, a hydroxyl group, and a carboxyl group.
[0006] Optionally, the particle size distribution range of the amphiphilic carbon dots is 1-10 nm; when excited by ultraviolet light, a fluorescence emission peak with a wavelength of 450-480 nm is generated, and the carbon dots do not lose weight below 250°C.
[0007] In the second aspect, a method for preparing amphiphilic carbon dots, preparing the amphiphilic carbon dots described in any of the above-mentioned first aspect, comprising: using C12-C18 long-chain fatty acids or a mixture of C12-C18 long-chain fatty acids and glycerol as a precursor or a mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds as a precursor, and hydrogen peroxide as an oxidant, uniformly mixing the precursor, the oxidant, and the solvent to form a homogeneous solution, reacting at 160-210°C for 4-8h, and after the reaction is completed, cooling to room temperature, and separating and purifying to obtain amphiphilic carbon dots; the nitrogen-containing compounds include one or more of o-phenylenediamine, m-phenylenediamine, hydroquinone, urea, aniline, and nitrobenzene.
[0008] Optionally, the solvent includes one or more of water, ethanol, acetone, and N,N-dimethylformamide.
[0009] Optionally, the separation and purification method is to obtain the amphiphilic carbon dots by dialysis followed by rotary evaporation.
[0010] Optionally, the mass ratio of the precursor to hydrogen peroxide is 1:1-1:5.
[0011] Optionally, the mass ratio of C12-C18 long-chain fatty acids to glycerol in the mixture of C12-C18 long-chain fatty acids and glycerol is 5:1-1:5; or, the mass ratio of C12-C18 long-chain fatty acids to nitrogen-containing compounds in the mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds is 5:1-1:5.
[0012] In a third aspect, a surfactant composition is provided, comprising amphiphilic carbon dots prepared by the amphiphilic carbon dots described in any one of the first aspect or the amphiphilic carbon dots prepared by the preparation method of any one of the second aspect, and a cationic surfactant.
[0013] Optionally, the cationic surfactant includes one or more of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and dodecyldimethylbenzylammonium chloride.
[0014] In a fourth aspect, a method for preparing a surfactant composition, for preparing any surfactant composition described in the third aspect, comprising: mixing amphiphilic carbon dots and cationic surfactants and adding them into water to dissolve, wherein the mass ratio of the amphiphilic carbon dots to the cationic surfactants is 1:9-9:1.
[0015] Beneficial effects:
[0016] (1) In the present invention, amphiphilic carbon dots are prepared using C12-C18 long-chain fatty acids as precursors and hydrogen peroxide as an oxidant. C12-C18 long-chain fatty acids can provide hydrophobic long carbon chains. The addition of hydrogen peroxide helps to form hydrophilic groups on the surface of carbon dots, thereby balancing the hydrophilicity and hydrophobicity, making them have significant surface activity. Using biomass-based C12-C18 long-chain fatty acids as precursors, the raw material source is renewable and has the characteristics of green chemistry. The oxidant in the preparation process is hydrogen peroxide, and the decomposition products are water and oxygen, which is environmentally friendly.
[0017] (2) In the present invention, the amphiphilic carbon dots have bright blue fluorescence with an emission peak at about 450nm; they can be evenly dispersed in water and organic phases in a spherical shape; the long carbon chains on the surface and the graphene-like structure of the carbon core make the carbon dots resistant to high temperatures and do not lose weight below 250°C; the carbon dots are negatively charged and have good wetting ability; the electrostatic attraction between the cationic surfactant and the carbon dots in the surfactant composition makes the oil removal effect significantly better than CTAB, carbon dots, SDS, AEO-9 and CAB-30 surfactants at the same concentration;
[0018] (3) In the present invention, firstly, the negatively charged carbon dots and the cationic surfactants form a strong electrostatic attraction, which significantly enhances the synergistic effect between the two. This synergistic effect reduces the critical micelle concentration (CMC) of the surfactant, and can exert a strong decontamination ability even at a lower concentration, thereby reducing the cost of use and improving the adsorption efficiency of the surfactant. In addition, the negatively charged carbon dots can effectively reduce the oil-water interfacial tension and accelerate the emulsification and stripping process of the oil stains. The charge density on the surface of the carbon dots regulates the interfacial environment, making it easier for the oil stain particles to desorb from the substrate surface and disperse in the aqueous phase. In addition, the wetting ability of the carbon dots enables them to quickly spread to the contaminated surface, converting the hydrophobic oil stains into a hydrophilic surface. The wetting ability also enables the carbon dots to penetrate into complex surfaces or tiny gaps, effectively treating stubborn oil stains or residues on irregular substrates. After electrostatic attraction, the surfactant composition has a strong dispersion stability, which can inhibit the oil stains that have detached from the substrate from being deposited on the surface again, thereby improving the thoroughness of cleaning and the degreasing effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the structure of the amphiphilic carbon dots of the present invention;
[0020] Figure 2 The UV-visible absorption, fluorescence excitation and emission spectra of the amphiphilic carbon dots of the present invention are ( Figure 2 (a)), excitation-dependent fluorescence image ( Figure 2 (b));
[0021] Figure 3 This is a high-resolution transmission electron microscopy image of the amphiphilic carbon dots (0.5 mg / mL) in ethanol solution and aqueous solution ( Figure 3 (a) is the dispersion diagram of carbon dots in ethanol solution. Figure 3 (b) is the dispersion diagram of carbon dots in aqueous solution; Figure 3 The lower left corner of (a) is the particle size distribution diagram. Figure 3 The upper right corner of (a) is the lattice diffraction pattern. Figure 3 The upper right corner of (b) is an enlarged image);
[0022] Figure 4 The particle size changes of the amphiphilic carbon dots in different alcohol solvents in the present invention;
[0023] Figure 5 It is the infrared spectrum of the amphiphilic carbon dots and linoleic acid of the present invention;
[0024] Figure 6 is the nuclear magnetic resonance spectrum of the amphiphilic carbon dots of the present invention ( Figure 6 (a) is the H NMR spectrum of amphiphilic carbon dots. Figure 6 (b) is the NMR carbon spectrum of amphiphilic carbon dots);
[0025] Figure 7 This is a Raman spectrum of the amphiphilic carbon dots of the present invention;
[0026] Figure 8 This is the thermal gravimetric curve of the amphiphilic carbon dots of the present invention.
[0027] Fig. 9 It is the Zeta potential diagram of the amphiphilic carbon dots applied in the present invention.
[0028] Fig.10 This is a contact angle photograph of the amphiphilic carbon dot surfactant applied in the present invention.
[0029] Fig.11 It is the infrared spectrum of the carbon dots prepared in Example 6 of the present application.
[0030] Fig.12 The hydrophilicity and hydrophobicity of the carbon dots prepared in Comparative Example 1 of the present invention are characterized ( Fig.12 The left picture in (a) shows the dispersion of carbon dots in water (left) and ethanol (right). Fig.12(b) is a schematic diagram of the extraction experiment. Fig.12 (c) Schematic diagram of contact angle size).
[0031] Fig.13 It is a curve diagram of reducing the surface tension of pure water by various types of amphiphilic surfactants applied in the present invention.
[0032] Fig.14 This is a comparison chart of the oil removal rates of various amphiphilic surfactants used in the present invention.
[0033] Fig.15 It is a schematic diagram of the CMC curve of the carbon dot CTAB compound mixed system applied for in the present invention. DETAILED DESCRIPTION
[0034] It is worth noting that the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0035] Determination of oil pollution removal effect:
[0036] Refer to the operation of national standard GBT35833-2018, the specific method is as follows:
[0037] (1) Preparation of artificial dirt
[0038] Recipe: 64.0g soybean oil, 8.0g ammonia-free caramel color, 12.0g wheat flour, 8.0g lard, 8.0g butter, 2.4g glyceryl monostearate.
[0039] Weigh soybean oil, butter, lard and glyceryl monostearate in a 250mL plastic beaker, heat in a water bath at 70℃ to dissolve; add ammonia-free caramel color while stirring and cool to 30℃, stir at a speed of not less than 1000r / min for 30min, add wheat flour after emulsification, stir for another 10min, age for 24h, store in a refrigerator for later use, and return to 20℃~25℃ before use.
[0040] Note 1: The shelf life of artificial dirt in the refrigerator is half a month.
[0041] Note 2: The detergency test results of some actual samples will change as the storage period of the dirt increases. Therefore, the test results are marked with the date of dirt production and use to facilitate result traceability.
[0042] (2) Preparation of dirty sheets
[0043] 1Cr18Ni9Ti brushed stainless steel (50mm×50mm×3mm) was selected as the test specimen. The specimen was cleaned, dried in an oven at 120℃ for 1h, cooled to room temperature, and weighed on an analytical balance, recorded as M. Use a brush to evenly apply oil stains on the specified parts of the specimen, and the dirt mass is controlled at 20-100mg / piece. After coating, it was dried in an oven at 150℃ for 15min. After cooling, it was placed in a UV constant temperature aging box and irradiated at 45℃ for 1h. After the test, the specimen was taken out, dried and aged in a dryer for 10h, and weighed, recorded as M1. The prepared test specimen was clamped on the swing washing rack of the swing washing machine, and a stopwatch was used to time the time. The oil stain part was completely immersed in the carbon dot solution (5mg / mL) for 10min, swing washed for 10min, and then swing washed in clean water for 1min. The specimen was removed, dried in an oven at 120℃ for 30min, and weighed after cooling to room temperature, recorded as M2. Three test pieces were used for each sample and the measurement was performed three times in parallel.
[0044] (3) Calculation of detergency
[0045] Detergency is the efficiency of removing oil stains, expressed in %, and the calculation formula is:
[0046]
[0047] Where: M is the mass of the test piece, in grams (g); M1 is the mass of the dirty piece before washing, in grams (g); M2 is the mass of the dirty piece after washing, in grams (g). It is advisable that the absolute difference between the two test results obtained under repeated conditions is no more than 3%, and the arithmetic mean of the test data is taken as the detergency result.
[0048] Description of the preparation method of amphiphilic carbon dots
[0049] A method for preparing amphiphilic carbon dots comprises: using C12-C18 long-chain fatty acids or a mixture of C12-C18 long-chain fatty acids and glycerol as a precursor or a mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds as a precursor, and hydrogen peroxide as an oxidant, uniformly mixing the precursor, the oxidant, and a solvent to form a homogeneous solution, reacting at 160-210° C. for 4-8 hours, cooling to room temperature after the reaction is completed, and separating and purifying to obtain amphiphilic carbon dots.
[0050] Optionally, the solvent includes one or more of water, ethanol, acetone, and N,N-dimethylformamide.
[0051] Optionally, the separation and purification method is to obtain the amphiphilic carbon dots by dialysis followed by rotary evaporation.
[0052] Optionally, the mass ratio of the precursor to hydrogen peroxide is 1:1-1:5.
[0053] In some embodiments, the mass ratio of the precursor to hydrogen peroxide H2O2 is 1:1.
[0054] In some embodiments, the mass ratio of the precursor to hydrogen peroxide H2O2 is 1:5.
[0055] Optionally, the mass of hydrogen peroxide is 2.2 g or 3.3 g.
[0056] In some embodiments, the C12-C18 long chain fatty acids include saturated fatty acids or unsaturated fatty acids.
[0057] In some embodiments, the saturated fatty acids include one or more of lauric acid, myristic acid, palmitic acid, and stearic acid; the unsaturated fatty acids include one or more of oleic acid, linoleic acid, and linolenic acid.
[0058] In some embodiments, the volume of the solvent is determined according to the volume of the reaction kettle. For example, the volume of the solvent in a 25 mL reaction kettle is approximately 8-15 mL.
[0059] Optionally, the mass ratio of C12-C18 long-chain fatty acids to glycerol in the mixture of C12-C18 long-chain fatty acids and glycerol is 5:1-1:5; or, the mass ratio of C12-C18 long-chain fatty acids to nitrogen-containing compounds in the mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds is 5:1-1:5, and the nitrogen-containing compounds include one or more of o-phenylenediamine, m-phenylenediamine, hydroquinone, urea, aniline, and nitrobenzene.
[0060] In some embodiments, the mass ratio of C12-C18 long-chain fatty acids to glycerol in the mixture of C12-C18 long-chain fatty acids and glycerol is 5:1.
[0061] In some embodiments, the mass ratio of C12-C18 long-chain fatty acids to glycerol in the mixture of C12-C18 long-chain fatty acids and glycerol is 1:5.
[0062] In some embodiments, the mass ratio of C12-C18 long-chain fatty acids to glycerol in the mixture of C12-C18 long-chain fatty acids and glycerol is 3:1 or 2:1.
[0063] In some embodiments, the mass ratio of C12-C18 long-chain fatty acids to nitrogen-containing compounds in the mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds is 5:1.
[0064] In some embodiments, the mass ratio of C12-C18 long-chain fatty acids to nitrogen-containing compounds in the mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds is 1:5.
[0065] In some embodiments, the mass ratio of C12-C18 long-chain fatty acids to nitrogen-containing compounds in the mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds is 3:1, or 2:1, or 1:1.5.
[0066] In some embodiments, the C12-C18 long chain fatty acid is 0.45 g or 0.62 g.
[0067] In some embodiments, the glycerol is 0.2 g or 0.3 g.
[0068] In some embodiments, the nitrogen-containing compound is 0.40 g or 0.60 g.
[0069] Example 1: Preparation of carbon dots using linoleic acid as a precursor
[0070] Weigh 0.45g linoleic acid, measure 2.2g H2O2, add to 8mL DMF (i.e. N, N-dimethylformamide, Dimethy lformamide, referred to as DMF, the same below), and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 160℃ for 6h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0071] Example 2: Preparation of carbon dots using lauric acid as precursor
[0072] Weigh 0.62g of lauric acid, measure 2.2g of H2O2, add to 8mL of DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then place the reactor in an oven and react at 180°C for 7h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0073] Example 3: Preparation of carbon dots using oleic acid as a precursor
[0074] Weigh 0.80g oleic acid, measure 2.2g H2O2, add to 8mL DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 180℃ for 6h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0075] Example 4: Preparation of carbon dots using oleic acid and glycerol as precursors
[0076] Weigh 0.65g oleic acid and 0.2g glycerol, measure 2.2g H2O2, add to 8mL DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 200℃ for 6h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0077] Example 5: Preparation of carbon dots using linoleic acid and glycerol as precursors
[0078] Weigh 0.45g linoleic acid and 0.30g glycerol, measure 2.2g H2O2, add to 8mL DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 160℃ for 6h. After the reaction is completed, cool to room temperature. The crude product is purified by column chromatography (silica gel column, eluent is ethyl acetate and petroleum ether, the volume ratio is 2:1), collect the fluorescent components, and obtain the carbon dot sample after rotary evaporation.
[0079] Example 6: Preparation of carbon dots using linoleic acid and o-phenylenediamine as precursors
[0080] Weigh 0.45g linoleic acid and 0.40g o-phenylenediamine, measure 2.2g H2O2, add to 10mL DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 180°C for 6h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0081] Example 7: Preparation of carbon dots using lauric acid and urea as precursors
[0082] Weigh 0.62g of lauric acid and 0.4g of urea, measure 2.8g of H2O2, add to 8mL of DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 160°C for 8h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0083] Example 8: Preparation of carbon dots using oleic acid and nitrobenzene as precursors
[0084] Weigh 0.45g linoleic acid and 0.60g nitrobenzene, measure 3.3g H2O2, add to 10mL DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 180℃ for 8h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0085] Example 9: Preparation of carbon dots using linoleic acid and aniline as precursors
[0086] Weigh 0.45g linoleic acid and 0.40g aniline, measure 2.2g H2O2, add to 10mL DMF, and mix evenly by ultrasonication. Transfer the mixture to a polytetrafluoroethylene reactor, then put the reactor into an oven and react at 180℃ for 6h. After the reaction is completed, cool to room temperature. The crude product is dialyzed and purified (molecular weight cutoff is 1000-3500Da), and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0087] Comparative Example 1: Preparation method of carbon dots using linoleic acid as precursor without adding hydrogen peroxide
[0088] Weigh 0.45 g of linoleic acid, add it to 8 mL of DMF, mix it by ultrasonication, transfer the mixture to a polytetrafluoroethylene reactor, put the reactor into an oven, and react for 6 h at 160 ° C. After the reaction is completed, cool to room temperature, and dialysis and purification of the crude product (molecular weight cutoff is 1000-3500 Da) are performed, and the obtained solution is rotary evaporated to obtain a carbon dot sample.
[0089] Description of amphiphilic carbon dots
[0090] like Figure 1 As shown, an amphiphilic carbon dot, the amphiphilic carbon dot includes a crystalline sp 2 Or amorphous sp 3 The hybridized carbon has a conjugated structure in the carbon core portion and has a hydrophilic group and a C12-C18 hydrophobic alkane chain on the surface, wherein the hydrophilic group includes an amino group, a hydroxyl group, and a carboxyl group.
[0091] In some embodiments, the hydrophilic group includes at least one of an amino group, a hydroxyl group, and a carboxyl group.
[0092] Optionally, the particle size distribution range of the amphiphilic carbon dots is 1-10 nm; when excited by ultraviolet light, a fluorescence emission peak with a wavelength of 450-480 nm is generated, and the carbon dots do not lose weight below 250°C.
[0093] In some embodiments, the carbon dots obtained in Example 1 using linoleic acid as a precursor are detected.
[0094] like Figure 2 As shown, the carbon dots have bright blue fluorescence with an emission peak at around 450 nm; and the emission peak wavelength has a clear excitation-dependent property.
[0095] like Figure 3 As shown, the carbon dots are evenly dispersed and spherical, with an average particle size of about 1.9 nm; Figure 3 (a) shows that the carbon dot structure has obvious lattice fringes with a spacing of 0.20 nm, corresponding to the (100) lattice plane of graphene carbon, indicating that the carbon dots contain graphene carbon; the particle size of the carbon dots in water is larger than that in ethanol solution, indicating that the carbon dots have better dispersibility in ethanol.
[0096] like Figure 4 As shown in the figure, under the same alcohol solvent conditions, the hydrated particle size of 0.05mg / mL carbon dots is smaller than that of 0.5mg / mL carbon dots, and the hydrated particle size of 0.05mg / mL carbon dots in ethanol (Ethano l) is larger than the particle size measured in TEM (transmission electron microscopy), indicating that the carbon dots have aliphatic carbon chains on the surface, forming a larger hydration layer. The dispersibility of carbon dots of different concentrations in long-chain alcohols is better than that of short-chain alcohols; the hydrated particle size of 0.05mg / mL carbon dots in dodecano l is almost the same as 1.9nm in TEM (transmission electron microscopy), indicating that carbon dots and dodecano l have excellent compatibility and the two have the same structure, which indirectly proves that there are long carbon chains above C12 on the surface of carbon dots.
[0097] like Figure 5 As shown in the figure, the structures of the carbon dot precursor (linoleic acid) and the carbon dots are compared at 3480 cm -1 、2850-2950cm -1 、1640cm -1 、1480cm -1 The absorption peaks at 1100cm-1 are attributed to -OH stretching vibration, asymmetric and symmetric stretching vibrations of CH bonds in -CH3 and -CH2, -C=O symmetric stretching vibration, CH2=CH2 symmetric stretching vibration, and C-O-C symmetric stretching vibration. The carbon dot structure inherits the characteristics of the precursor, and contains hydrophilic functional groups (-OH, -COOH) and hydrophobic carbon chains (containing carbon chains above C12) on the surface.
[0098] like Figure 6As shown, the proton signals in carbon dots are always broad and weak, which is the difference from small molecules. In the H-NMR spectrum, the signals at chemical shifts of 0 to 2 ppm correspond to the hydrogen on the alkyl group in the aliphatic carbon chain, the signals between 6 and 8 ppm correspond to the hydrogen on the benzene ring, and the signals at 2.0-2.5 ppm and 4-5 ppm correspond to the unsaturated carbon chain -CH2-CH=CH2. In the C-NMR spectrum, the signals at 20–40, 130, and 170 ppm correspond to the carbon in the aliphatic carbon chain, –CH2=CH2, and –COOH functional groups, respectively. The above data prove that the carbon dot structure contains hydrophilic functional groups (-COOH), hydrophobic aliphatic carbon chains, benzene rings, and unsaturated carbon structures.
[0099] like Figure 7 As shown in the figure, the D-band and G-band absorption peaks correspond to the irregular sp3 carbon skeleton structure and the ordered graphitized sp2 carbon structure in the carbon dots, which are similar to the lattice structure of graphite materials.
[0100] like Figure 8 As shown, curve 1 is the thermal weight loss curve of carbon dots, and curve 2 is the differential thermogravimetric curve of carbon dots. It can be seen from curve 1 that no mass loss of carbon dots was observed before reaching 250°C; the starting point of thermal weight loss of general carbon dots is mostly around 100°C, and there are few reports of the first stage thermal weight loss temperature of carbon dots at 200°C, indicating that the carbon dots prepared in the embodiment of the present invention have good thermal stability. The mass loss between 200-300°C is more than 70%, and the differential thermogravimetric curve shows an obvious degradation peak at around 280°C, corresponding to the dissociation of oxygen-containing functional groups such as hydroxyl and carboxyl, and the dissociation of long carbon chains occurs in the range of 300°C-450°C; the temperature continues to rise, and the residual mass no longer changes, indicating that the graphene-like structure in the carbon dots is resistant to high temperatures.
[0101] like Fig. 9 As shown in , the carbon dot aqueous solution is negatively charged; Fig.10 As shown, a carbon dot aqueous solution is dropped onto the surface of a test piece. After the film is formed, a pure water droplet is dropped and the contact angle of the droplet on the test piece surface is measured. Fig.10 The medium contact angle is 65.3°, which indicates that the droplet can spread on the surface of the specimen and the carbon dots have good wetting ability.
[0102] In some embodiments, the carbon dots obtained in Example 6 using linoleic acid and o-phenylenediamine as precursors are detected.
[0103] like Fig.11 As shown in the figure, the prepared amphiphilic carbon dots have a wavelength of 3500 cm -1 、3200cm -1 、2900-2950cm -1 、1640cm -1 、1480cm -1、1100cm -1 The absorption peaks at are respectively attributed to -OH stretching vibration, -NH2 stretching vibration, asymmetric and symmetric stretching vibration of CH bonds in -CH3 and -CH2, -C=O / -C=N symmetric stretching vibration, CH2=CH2 symmetric stretching vibration, and C-O-C symmetric stretching vibration, indicating that the surface of carbon dots contains hydrophilic functional groups (-OH, -NH2, -COOH) and hydrophobic carbon chains.
[0104] like Fig.12 As shown in (a), the carbon dots disperse poorly in water, but disperse completely in ethanol, indicating that the carbon dots have poor hydrophilicity. Using toluene as the extractant, by monitoring the blue fluorescence of the carbon dots, it can be seen that most of the carbon dots are extracted from water into the upper toluene, further indicating that the carbon dots have strong hydrophobicity ( Fig.12 The contact angle of 101.4° in the contact angle experiment also shows that the carbon dots are hydrophobic and not amphiphilic ( Fig.12 As shown in (c), no hydrogen peroxide was added in Comparative Example 1, which indicates that the addition of hydrogen peroxide helps to form hydrophilic groups on the surface of carbon dots, thereby balancing the hydrophilicity and hydrophobicity.
[0105] Description of surfactant composition and preparation method thereof
[0106] A surfactant composition comprises any of the amphiphilic carbon dots described in the above description of amphiphilic carbon dots or two amphiphilic carbon dots prepared by any amphiphilic carbon dot preparation method, and a cationic surfactant.
[0107] Optionally, the cationic surfactant includes one or more of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and dodecyldimethylbenzylammonium chloride.
[0108] A method for preparing a surfactant composition, preparing any of the above-mentioned surfactant compositions, comprising: mixing amphiphilic carbon dots and cationic surfactants and adding them into water for dissolution, wherein the mass ratio of the amphiphilic carbon dots to the cationic surfactants is 1:9-9:1.
[0109] Optionally, the mass ratio of the amphiphilic carbon dots to the cationic surfactant is 1:9-1:1.
[0110] Optionally, the mass ratio of the amphiphilic carbon dots to the cationic surfactant is 1:1.
[0111] Example 10: Preparation of a surfactant composition comprising amphiphilic carbon dots and hexadecyltrimethylammonium bromide (CTAB, a cationic surfactant)
[0112] Using the carbon dots prepared in Example 1, equal masses of carbon dots and cetyltrimethylammonium bromide (CTAB) were weighed and added into 100 mL of water in total amounts of 10, 100, 300 and 500 mg, respectively. After ultrasonic treatment, CTAB and carbon dots were completely dissolved to obtain the composite solution to be tested, and the total concentration of active substances was 0.1, 1, 3 and 5 mg / mL, respectively.
[0113] Example 11: Preparation of a surfactant composition comprising amphiphilic carbon dots and octadecyltrimethylammonium chloride (STAC, cationic surfactant)
[0114] Using the carbon dots prepared in Example 1, the carbon dots and STAC were weighed in a mass ratio of 4:6, and added into 100 mL of water at a total amount of 10, 100, 300 and 500 mg, respectively. After ultrasonic treatment, STAC and carbon dots were completely dissolved to obtain the composite solution to be tested, and the total concentration of active substances was 0.1, 1, 3 and 5 mg / mL, respectively.
[0115] Example 12: Preparation of a surfactant composition comprising amphiphilic carbon dots and dodecyltrimethylammonium bromide (DTAB, cationic surfactant)
[0116] Using the carbon dots prepared in Example 1, the carbon dots and DTAB were weighed in a mass ratio of 3:7, and added into 100 mL of water in a total amount of 10, 100, 300 and 500 mg, respectively. After ultrasonic treatment, DTAB and carbon dots were completely dissolved to obtain the composite solution to be tested, and the total concentration of active substances was 0.1, 1, 3 and 5 mg / mL, respectively.
[0117] Example 13: Preparation of a surfactant composition comprising amphiphilic carbon dots and dodecyl dimethyl benzyl ammonium chloride (1227, cationic surfactant)
[0118] Using the carbon dots prepared in Example 1, equal masses of carbon dots and 1227 were weighed and added into 100 mL of water in total amounts of 10, 100, 300 and 500 mg, respectively. After ultrasonic treatment, 1227 and carbon dots were completely dissolved to obtain the composite solutions to be tested, and the total concentrations of active substances were 0.1, 1, 3 and 5 mg / mL, respectively.
[0119] Test Example 1: Decontamination Performance Test of Amphiphilic Carbon Dots
[0120] Using the carbon dots prepared in Example 1, 10, 100, 300 and 500 mg of carbon dots were weighed and added into 100 mL of water respectively. After stirring until the carbon dots were completely dispersed, the carbon dot surfactant solutions to be tested were prepared. The concentrations of the solutions were 0.1, 1, 3 and 5 mg / mL respectively. The oil removal effect was measured.
[0121] Comparative Example 2: Oil removal effect of CTAB:
[0122] Weigh 10, 100, 300 and 500 mg CTAB and add them into 100 mL water respectively. After ultrasonic treatment, CTAB is completely dissolved to obtain the surfactant solution to be tested. The concentrations of the surfactant solutions are 0.1, 1, 3 and 5 mg / mL respectively. The oil removal effect is measured.
[0123] Comparative Example 3: Oil removal effect of fatty acid polyoxyethylene ether-9 (AEO-9, nonionic surfactant):
[0124] Weigh 10, 100, 300 and 500 mg AEO-9 and add them into 100 mL water respectively. After stirring, AEO-9 is completely dissolved to obtain the surfactant solutions to be tested. The concentrations of the surfactant solutions are 0.1, 1, 3 and 5 mg / mL respectively. The oil removal effect is measured.
[0125] Comparative Example 4: Degreasing effect of sodium dodecyl sulfate (SDS, anionic surfactant):
[0126] Weigh 10, 100, 300 and 500 mg SDS and add them into 100 mL water respectively. After ultrasonic treatment, SDS is completely dissolved to obtain the surfactant solution to be tested. The concentrations of the solutions are 0.1, 1, 3 and 5 mg / mL respectively. The oil removal effect is measured.
[0127] Comparative Example 5: Oil removal effect of cocamidopropyl betaine (CAB-30, amphoteric surfactant):
[0128] Weigh 10, 100, 300 and 500 mg CAB-30 and add them into 100 mL water respectively. After stirring, CAB-30 is completely dissolved to obtain the surfactant solution to be tested. The concentrations of the surfactant solutions are 0.1, 1, 3 and 5 mg / mL respectively. The oil removal effect is measured.
[0129] like Fig.13 As shown in the figure, after adding CTAB, SDS, AEO-9 and CAB-30, the interfacial tension of pure water finally dropped from 72mN / m to about 35mN / m, while carbon dots can make the interfacial tension of water reach about 30, at which time the CMC is 0.1mg / mL; after carbon dots are compounded with CTAB, when the CMC drops to 0.05mg / mL, the interfacial tension is about 27mN / m, indicating that the performance of reducing the surface tension after compounding is better.
[0130] like Fig.14 As shown, when CTAB, carbon dots, SDS, AEO-9 and CAB-30 are used alone as degreasing agents, the degreasing effect of CTAB is the worst at all concentrations. However, in Example 10, after carbon dots and CTAB are mixed in equal amounts, the degreasing effect is better than other surfactants at the same concentration.
[0131] Test Example 2: Synergistic Effect of Cetyltrimethylammonium Bromide (CTAB, Cationic Surfactant) and Carbon Dots
[0132] When two surfactants are mixed, if the CMC value (i.e., critical micelle concentration) of the mixed system is between the CMC values of the two surfactants, then this mixed system is called an ideal mixed system; if the CMC value of the mixture may be lower than the CMC value of any component, then this mixed system has a synergistic or synergistic effect and is called a non-ideal mixed system.
[0133] For a binary ion system, assuming that the mixed micelle is an ideal mixture, the critical micelle concentration c of the ideal mixture is 12 satisfy:
[0134]
[0135] Wherein, α is the molar fraction of surfactant 1, c1 and c2 are the critical micelle concentrations of surfactant 1 and surfactant 2, respectively, and K0 is the correction coefficient of the ionic surfactant system.
[0136] Combining the surface tension measurement and oil removal experiments, it can be seen that the composite system of carbon dots and CTAB is exactly this non-ideal binary surfactant mixed system. Fig.15 As shown in the figure, if CTAB and carbon dots are an ideal mixed system, according to the critical micelle concentration c of the ideal mixture 12 By calculation, the CMCidea l curve (i.e., CMC ideal mixing curve) of CTAB and carbon dots can be obtained, wherein carbon dot CTAB mixed solutions with carbon dot mass fractions of 0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1.0 are prepared, and then the CMC values of the above carbon dot mass fraction series of mixed solutions are tested using the K11 surface tension meter of the German Krüss Company, and the CMCexp curve is obtained. It is obvious that the actual experimental results deviate far from the ideal system. The reason is due to the electrostatic attraction between cationic CTAB and carbon dots, which in turn produces a synergistic effect or synergistic effect.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention application and are not intended to limit it. Although the present invention application has been described in detail with reference to the preferred embodiments, the combination of different embodiments falls within the scope of protection of the present invention application. Those skilled in the art should understand that the technical solutions of the present invention application can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention application, which should be included in the scope of the claims of the present invention application.
Claims
1. An amphiphilic carbon dot, characterized in that: Amphiphilic carbon dots include crystalline sp 2 Or amorphous sp 3 The hybridized carbon has a conjugated structure in the carbon core portion and has a hydrophilic group and a C12-C18 hydrophobic alkane chain on the surface, wherein the hydrophilic group includes an amino group, a hydroxyl group, and a carboxyl group.
2. The amphiphilic carbon dot according to claim 1, characterized in that: The particle size distribution range of the amphiphilic carbon dots is 1-10 nm; when excited by ultraviolet light, a fluorescence emission peak with a wavelength of 450-480 nm is generated, and the carbon dots do not lose weight below 250°C.
3. A method for preparing amphiphilic carbon dots, comprising preparing the amphiphilic carbon dots according to any one of claims 1 to 2, characterized in that: include: Using C12-C18 long-chain fatty acids or a mixture of C12-C18 long-chain fatty acids and glycerol as a precursor or a mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds as a precursor, and hydrogen peroxide as an oxidant, the precursor, the oxidant, and the solvent are uniformly mixed to form a homogeneous solution, and the solution is reacted at 160-210° C. for 4-8 hours. After the reaction is completed, the solution is cooled to room temperature, and the amphiphilic carbon dots are separated and purified; the nitrogen-containing compounds include one or more of o-phenylenediamine, m-phenylenediamine, hydroquinone, urea, aniline, and nitrobenzene.
4. The method for preparing amphiphilic carbon dots according to claim 3, characterized in that: The solvent includes one or more of water, ethanol, acetone, and N,N-dimethylformamide.
5. The method for preparing amphiphilic carbon dots according to claim 3, characterized in that: The separation and purification method is to obtain the amphiphilic carbon dots by dialysis followed by rotary evaporation.
6. The method for preparing amphiphilic carbon dots according to claim 3, characterized in that: The mass ratio of the precursor to hydrogen peroxide is 1:1-1:
5.
7. The method for preparing amphiphilic carbon dots according to claim 3, characterized in that: The mass ratio of C12-C18 long-chain fatty acids to glycerol in the mixture of C12-C18 long-chain fatty acids and glycerol is 5:1-1:5; or, the mass ratio of C12-C18 long-chain fatty acids to nitrogen-containing compounds in the mixture of C12-C18 long-chain fatty acids and nitrogen-containing compounds is 5:1-1:
5.
8. A surfactant composition, characterized in that The surfactant composition comprises the amphiphilic carbon dots described in any one of claims 1 to 2 or the amphiphilic carbon dots prepared by the preparation method of the amphiphilic carbon dots described in any one of claims 3 to 7, and a cationic surfactant.
9. A surfactant composition according to claim 8, characterized in that: The cationic surfactant includes one or more of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and dodecyldimethylbenzylammonium chloride.
10. A method for preparing a surfactant composition, characterized in that: The preparation of the surfactant composition according to any one of claims 8 to 9 comprises: mixing the amphiphilic carbon dots and the cationic surfactant and adding them into water for dissolution, wherein the mass ratio of the amphiphilic carbon dots to the cationic surfactant is 1:9-9:1.